Determinants of Inflation in Nepal - Parajuli, Resham Bahadur Thapa (PYC Nepal Journal of Management, 2010)
The price level and its growth, inflation, is an important economic indicator. The main focus for measuring the cost of living is placed on CPI. This is because CPI measures inflation impact which is the final measure of prices on households. As the purchasing power of the monetary unit becomes less predictable, people resort to other means to carry out their business, means which use up resources and are inefficient. The current inflation in Nepal is running in double digit figure and is considered alarming. To address this problem is very important for a country like ours where the country is still struggling for the economic stability and growth. Using secondary data, this study tries to analyze the determinants of the inflation in Nepal considering CPI as inflation measuring rod.